Análisis de factibilidad de un sistema web para la configuración de la olt daytai de la empresa ISP Maxitel del cantón Vinces - Cañarte Tamayo, Laura Edaena (2020)
The purpose of this research is to carry out a feasibility analysis for the implementation of a web system for the configuration of the OLT Daytai of the company ISP Maxitel, which is located in the Vinces canton, Los Ríos province. After being able to verify the inconvenience that the employees of the technical department had, when configuring the olt, because it is a Chinese brand, so there is not much information about it. The settings of the olt are made through a console, and this causes technicians to make mistakes when making such configurations and waste of time, making this inconvenience a great problem for technicians and directly for the company. The web system aims to systematize the configuration processes, making them more reliable and error-free by technicians when configuring.